Pre-Service Teachers Beliefs about Plagiarism: An Attribution Theory Lens - Goegan, Lauren; Daniels, Lia M. (Canadian Perspectives on Academic Integrity, 2023)
There is a growing body of research examining why students engage in plagiarism, and what they know about plagiarism, but little of this research is conducted from a theoretical perspective. Moreover, the perspectives of preservice teachers are important to investigate as they have been described as the “future gatekeepers of academic integrity” (Fontaine et al., 2020). Therefore, the purpose of this study was twofold. First, to examine the opinions of preservice teachers in terms of what constitutes plagiarism. Second, following the principles of Attribution Theory, to investigate how the controllability (e.g., intentional, or accidental plagiarism) of the act of plagiarism impacted participants' beliefs concerning (a) responsibility, (b) emotions, (c) help-giving, and (d) reporting. We used a within-person repeated measures design with three levels of controllability manipulated through hypothetical scenarios of plagiarism to collect data from 201 pre-service teachers. Overall, preservice teachers had strong opinions about plagiarism (e.g., It is always wrong to plagiarize). Moreover, when scenarios included students who engaged in plagiarism that was controllable, participants were more likely to perceive the student as responsible, felt anger towards them, support punishment, and recommend reporting the student, than when the act of plagiarism was not seen as controllable. We provide recommendations for instructors and administrators for supporting students. Moreover, the results and recommendations here will be used to foster discussion about the controllability of cheating and the associated cognitions, emotions, and actions. This conversation will address fostering a culture of academic integrity from a theoretical perspective to support faculty and students.